Атлас мира для школьника: [перевод с английского] / Ф. Стил - Стил Филип (ОЛМА-ПРЕСС, 2000)
Экземпляры: (20160422) / Инвентарный номер: 28322 / Цена: / Сис.шифр: 26.89 / Авт.знак: С 80 / ББК: 26.89(0)я6